The impact of exercise self-efficacy on college students' emotion management ability: an analysis of the mediating effects based on exercise behavior and screen media use - Weidong Zhu; Bo Li; Hu Lou; Fanzheng Mu; Jun Liu (Frontiers Media S.A., 2024)
ObjectiveTo explore the impact of exercise self-efficacy on college students' emotion management ability and to analyze the mediating effects of exercise behavior and screen media use between exercise self-efficacy and emotion management ability.MethodsThis study adopted stratified, whole-cluster, and staged sampling methods, using an online questionnaire that included demographic information, exercise self-efficacy, exercise behavior, screen media use, and other relevant aspects, obtaining a total of 12,687 valid questionnaires.ResultsThe study indicated a significant positive correlation between exercise self-efficacy and emotion management ability (r = 0.349, p < 0.01). There was also a positive correlation between physical exercise and emotion management ability (r = 0.128, p < 0.01). In contrast, smartphone use showed a significant negative correlation with emotion management ability (r = −0.102, p < 0.01). Additionally, exercise persistence and electronic health literacy presented significant positive correlations with emotion management ability (r = 0.370, p < 0.01; r = 0.502, p < 0.01). Chain-mediated effect analysis revealed that exercise self-efficacy positively affected emotion management ability by enhancing physical exercise and reducing smartphone use (95% CI: [0.001, 0.002]). Furthermore, exercise self-efficacy positively influenced emotion management ability by enhancing exercise persistence and e-health literacy (95% CI: [0.029, 0.042]). These two variables acted as chain mediators, demonstrating the pathways through which exercise self-efficacy affects emotion management ability.ConclusionThis study deepened the understanding of the interplay between exercise behavior, screen media use, and emotion management ability. It suggested that emotion management ability could be enhanced through strategies of improving exercise persistence, physical exercise, electronic health literacy, and reducing smartphone use while considering differences in gender, academic year, and regional factors in intervention programs.